Contribution of Post-Pandemic Transformational Leadership towards Learning Loss - Rini, Riswanti; Riswandi, Riswandi; Izzatika, Amrina; Ningtyas, Ika Wulandari Utami; Azizah, Alif Luthvi; Handoko, Handoko (FKIP Universitas Lampung, 2023)
Post-pandemic Transformational leadership on Learning Loss Quality of Education. Objectives: The main problem of the research is a learning loss. The research aims to determine the effect of principal’s transformational leadership to solve learning loss problem. Methods: The research type was a quantitative. The population in this study was 1997 state junior high school teachers in Bandar Lampung. This research uses cluster random sampling with a total sample of 226 teachers. The data collection technique used questionnaire with a likert scale. The data were analyzed by using Pearson's Moment Product, Coefficient Correlation Pearson in SPSS and Kolmogorof Smirnov test. Findings: The results showed that each variable of transformational leadership could solve the problem of learning loss with a positive effect by 9,7%, while 90.3% was influenced by other unexamined variables. Conclusion: There was a positive effect of principal’s transformational leadership to solve learning loss problem. Keywords: principal’s transformational leadership, quality of education, learning loss.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202331